2021
DOI: 10.2147/cmar.s291085
|View full text |Cite
|
Sign up to set email alerts
|

Natural Orifice Specimen Extraction Surgery versus Conventional Laparoscopic-Assisted Resection in the Treatment of Colorectal Cancer: A Propensity-Score Matching Study

Abstract: Background Natural orifice specimen extraction surgery (NOSES) has been successfully applied to the treatment of gastric, colorectal cancer (CRC). However, the development of NOSES is still in the exploratory stage, and there is still no strong evidence-based medical evidence. Patients and Methods From January 2013 to June 2017, consecutive patients with colorectal cancer who underwent transluminal resection, anastomosis, and specimen extraction and those who underwent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 24 publications
1
16
0
Order By: Relevance
“…Both procedures are performed laparoscopically, except that the specimen is obtained in a different manner, and the two procedures are considered to have the same therapeutic effect. 29,30 We first verified that not only the number of CTCs will decrease, but also the proportion of M-CTCs will decrease significantly after surgery, which proves that surgery can reduce the proportion of M-CTCs.…”
mentioning
confidence: 79%
“…Both procedures are performed laparoscopically, except that the specimen is obtained in a different manner, and the two procedures are considered to have the same therapeutic effect. 29,30 We first verified that not only the number of CTCs will decrease, but also the proportion of M-CTCs will decrease significantly after surgery, which proves that surgery can reduce the proportion of M-CTCs.…”
mentioning
confidence: 79%
“…Laparoscopic radical resection for rectal cancer has been widely used, but the assisted incision in the abdominal wall could induce great trauma to the patients, which was not conducive to the postoperative recovery of the patient [ 18 , 19 ]. In recent years, with the development of minimally invasive technique, NOSES has become one of the most popular producers, which has the advantages of less trauma, shorter scar, shorter healing time, and fewer complications [ 20 , 21 ]. The results of this study showed that intraoperative blood loss, additional analgesic use, postoperative gastrointestinal recovery time, and hospital stay in the NOSES group were better than those in the conventional laparoscopic group.…”
Section: Discussionmentioning
confidence: 99%
“…There are now increasing numbers of related reports and patients undergoing this operation. Tang et al [ 16 ] found that the NOSES group had advantages in terms of reducing postoperative complications and postoperative pain, faster recovery of gastrointestinal function, and shorter postoperative hospital stay. Most notably, the physical function, role function, emotional function, and overall health status in the NOSES group were significantly better than those in the conventional laparoscopic surgery group.…”
Section: Current Situation Of Nosesmentioning
confidence: 99%
“…One patient developed a surgical site infection and one patient had fluid collection at the suture site which prolonged hospital stay to 8 d. Following a comparative analysis, the researchers believe that the NOSES technique is a promising, safe, and effective minimally invasive surgery. Recently, Tang et al [ 16 ] used a type of NOSES to perform Roux-en-Y reconstruction after laparoscopic total gastrectomy with two circular staplers (one of which was oval). The advantage of this technique is that it can be applied to the tumor located very close to the cardia.…”
Section: Research Progress and Application Prospects Of Noses In Gcmentioning
confidence: 99%